Pelaksanaan Pendidikan Kesehatan Mengenai Bahaya Keputihan untuk Meningkatkan Pengetahuan dan Sikap pada Remaja Putri: Studi Kasus - Dewi, Siti Utami; Putri, Deviana Azzahra (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Adolescence is a period of transition from childhood to adulthood. During adolescence, there is rapid growth, including reproductive organs. Health problems often occur in adolescent girls who are vaginal discharge. Vaginal discharge is a liquid that comes out of the vagina that is not blood. Pathological vaginal discharge that occurs at the age of adolescent girls will further increase the risk of cervical cancer in adulthood. Vaginal discharge in adolescent girls can be prevented by providing health education. This study aims to obtain an overview of the implementation of health education regarding vaginal discharge to increase family knowledge and attitudes in adolescent girls. This research design uses a descriptive method in the form of a case study. The results of this study indicate an increase in knowledge with an average of 76% in subject I and 63% in subject II, while an attitude of 75% in subject I and 71% in subject II. It can be concluded that health education can increase knowledge and attitudes about the dangers of vaginal discharge in adolescent girls. It is hoped that subjects will be able to maintain the cleanliness of the feminine area and immediately go to the nearest health facility if vaginal discharge is unusual.